Contracting for Space: Contract Practice in the European Space Sector - Smith, Lesley Jane; Baumann, Ingo (Routledge, 2011)
Recent significant developments in the European space sector have had an impact on business and the growth of national and European commercial space law. This book analyses and assesses the legal issues and key factors influencing the space sector in Europe. It is an up-to-date guide to the regulatory background of space projects and examines the typical legal problems which need to be solved by practitioners in the field. Taking into account public and commercial international law and practice, this book examines substantive issues of law specific to launchers, satellite manufacturers and space service providers with contributions from leading experts and practitioners in the field of European space law and policy.